The emergence of resistant pneumococcal meningitis—implications for empiric therapy. Issue 3 (1st September 2002) - McMaster, P; McIntyre, P; Gilmour, R; Gilbert, L; Kakakios, A; Mellis, C
Abstract : Background: Following the emergence of penicillin and cephalosporin resistant pneumococcal meningitis in the United States, inclusion of vancomycin in empiric therapy for all suspected bacterial meningitis was recommended by the American Academy of Pediatrics. Few data are available to evaluate this policy. Aims: To examine the management and clinical course in relation to antibiotic therapy of a large unselected cohort of children with pneumococcal meningitis in a geographic area where antibiotic resistance has recently increased. Methods: Retrospective review of all cases of pneumococcal meningitis in a defined population (Sydney, Australia), 1994–99. Results: A total of 104 cases without predisposing illnesses were identified; timing of lumbar puncture (LP) was known in 103. Resistance to penicillin increased from 0 to 20% over the study period. Only 57 (55%) had an early LP (prior to parenteral antibiotics); 55 (96%) had organisms on Gram stain. Severe disease (intensive care admission or death) increased significantly from 57 cases with early LP (28%) to 33 with delayed LP (42%) to 13 with no LP (62%). Evidence of pneumococcal infection was available within 24 hours in 85% of those with delayed or no LP. Outcome was not related to empiric vancomycin use, which increased from 5% prior to 1998 to 48% in 1999. Conclusion: LP is frequently delayed in pneumococcal meningitis. Based on disease severity, empiric vancomycin is most justified when LP is deferred. If an early LP is done, vancomycin can be withheld if Gram positive diplococci are not seen.